PENGARUH METODE EKSPERIMEN TERHADAP KEAKTIFAN DAN HASIL BELAJAR IPAS SISWA KELAS VI - Silvina Salsabila; Sari Yustiana (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Learning The teaching of Natural and Social Sciences (IPAS) in elementary schools is still dominated by conventional teaching methods, which result in suboptimal student engagement and cognitive learning outcomes. Previous studies have shown that the experimental method can improve student engagement or learning outcomes; however, research examining the simultaneous impact of the experimental method on both aspects in IPAS instruction under the Merdeka Curriculum remains limited. Therefore, this study is important to provide empirical evidence regarding the effectiveness of the experimental method in improving the quality of IPAS instruction. This study aims to determine the effect of the experimental method on student learning engagement and cognitive learning outcomes in sixth grade regarding the topic of Earth’s rotation and revolution. This study employs a quantitative approach using a pre-experimental design of the One-Group Pretest-Posttest type. Data collection techniques were conducted through observation and testing, while data analysis utilized descriptive statistical tests and the Paired Sample T-Test. The results of the study on 11 students showed that the application of the experimental method was able to increase the average level of student learning activity from 66.66% to 85.22%, with the category changing from active to very active. In addition, students’ cognitive learning outcomes also showed an increase in the average score from 50.18% to 67.63%, moving from the “fairly good” to the “good” category. These results were supported by a Paired Sample T-Test, which showed a Sig. (2-tailed) value of 0.001 < 0.05; thus, Ho was rejected and H1 was accepted, indicating a significant effect. The findings of this study imply that the application of the experimental method can support the implementation of IPAS learning that is more active, meaningful, and student-centered in accordance with the characteristics of the Merdeka Curriculum. Thus, the experimental method has a significant effect on students’ learning activity and cognitive learning outcomes in IPAS learning. ABSTRAK Pembelajaran Pembelajaran Ilmu Pengetahuan Alam dan Sosial (IPAS) di sekolah dasar masih didominasi oleh metode pembelajaran konvensional yang menyebabkan keaktifan dan hasil belajar kognitif belum optimal. Berbagai penelitian sebelumnya menunjukkan bahwa metode eksperimen mampu meningkatkan keaktifan belajar atau hasil belajar siswa, namun penelitian yang mengkaji pengaruh metode eksperimen terhadap kedua aspek tersebut secara simultan dalam pembelajaran IPAS pada Kurikulum Merdeka masih terbatas. Oleh karena itu, penelitian ini penting dilakukan untuk memberikan bukti empiris mengenai efektivitas metode eksperimen dalam meningkatkan kualitas pembelajaran IPAS. Penelitian ini bertujuan untuk mengetahui pengaruh metode eksperimen terhadap keaktifan belajar dan hasil belajar kognitif siswa kelas VI pada materi rotasi dan revolusi bumi. Penelitian ini menggunakan pendekatan kuantitatif dengan desain Pre-Experimental jenis One Group Pretest-Posttest Design. Teknik pengumpulan data dilakukan melalui observasi dan tes, sedangkan analisis data menggunakan uji statistik deskriptif dan uji Paired Sample T-Test. Hasil penelitian pada 11 siswa menunjukkan bahwa penerapan metode eksperimen mampu meningkatkan jumlah rata-rata keaktifan belajar siswa dari 66,66% menjadi 85,22% dengan kategori aktif menjadi sangat aktif. Selain itu, hasil belajar kognitif siswa juga mengalami peningkatan jumlah rata-rata dari 50,18% menjadi 67,63% dengan kategori cukup baik menjadi baik. Hasil tersebut diperkuat dengan uji Paired Sample T-Test yang menunjukkan nilai Sig. (2-tailed) = 0,001 < 0,05 sehingga Ho ditolak dan H1 diterima, yang berarti terdapat pengaruh yang signifikan. Temuan penelitian ini memberikan implikasi bahwa penerapan metode eksperimen dapat mendukung implementasi pembelajaran IPAS yang lebih aktif, bermakna, dan berpusat pada siswa sesuai dengan karakteristik Kurikulum Merdeka. Dengan demikian, metode eksperimen berpengaruh signifikan terhadap keaktifan belajar dan hasil belajar kognitif siswa pada pembelajaran IPAS.